A Discourse Analysis Of Students-Teacher Pattern Interaction In Elt Classroom - Wiwi Rhamadina; Alek Alek; Nida Husna; Didin Nuruddin Hidayat (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study aims to find patterns of interaction between students and teachers in ELT classes. Participants involved in this study were 32 students and one English teacher. This research is a qualitative research with a descriptive design. This relates to the use of language in a social context, namely interaction or dialogue between students and teachers. The author uses 2 types of instruments, namely observation using the blue print protocol and also recording all English learning activities in the ninth grade of SMP N Toboali. Then after making observations and obtaining all the required data, the authors conducted an analysis using FIAS (Flanders Interaction System Analysis) which consisted of 3 parts, namely the teacher's indirect influence, the teacher's direct influence and students' speech responses. The teacher's indirect influence consists of 3 kinds of interactions such as receiving feelings, praising encouragement, accepting or using student ideas, and asking questions. Then, the teacher's direct influence consists of lecturing or explaining, giving directions, and criticizing or justifying authority. The last is the student's response which consists of the student's speech response, student initiation, and silence. According to the research results, there are four types of classroom interaction research: content traffic, teacher control, teacher support, and student participation. Based on the results of the data found, it shows that the dominant pattern used in this study is student participation, with a total of 54 or 45% of utterances. Hence, it can be concluded that the students of ninth grade students at SMPN 3 Toboali were active during the teaching and learning process in class.